KINERJA PASAR DITINJAU DARI ASPEK KEPEMILIKAN MANAJERIAL KEPUTUSAN INVESTASI DAN KEBIJAKAN DIVIDEN - Fitri Yeni; Riri Mayliza (JURNAL PUNDI, 2017)
Performance of the company can be seen from two parts, namely financial performance and market performance. The Market Performent This study is  to examine  the effect of managerial ownership, investment decisions, and dividend policy to  market performance. Samples in this study are  manufacturing companies listed  on Indonesia Stock Exchange that provide dividends from  2013 until 2015. Samples were taken by using the technique of puposive sampling, the data were analyzed by using Panel Data Regresion method. The results showed that managerial ownership (KP) has a regression coefficient value of 0.173 and t count of 0.594 with probability  value 0.555> 0 So concluded managerial ownership has no significant effect to market performance , The results show that investment decision (PER) Has a regression coefficient value of 0,214 dan thitung 2,931 With probability value of 0,005 <0,05 , Dividend Policy (DPR) regression coefficient value of -0,187 and  thitung -3,422 With probability value of 0,001 <0,05 The results show that investment decision has positive and significant effect to market performance and dividend policy has negative and significant effect to market performance. Keywords: Managerial Ownership, Investment Decision, Dividend Policy, Market Performance